1982
DOI: 10.1152/jappl.1982.52.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive end-expiratory pressure and body position in unilateral lung injury

Abstract: Positive end-expiratory pressure (PEEP), by increasing lung volume in acute lung injury, may recruit terminal air spaces in the involved regions, but may also distend noninvolved regions increasing extravascular lung water and worsening gas exchange. We investigated the effect of increasing levels of PEEP on arterial oxygenation in 26 anesthesized dogs with unilateral acid pneumonitis and studied the influences of gravity and distribution of the injury on this effect. Arterial PO2 was consistently higher when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In some patients normal values of PEEP produce little improvement in oxygenation, whilst higher values may increase alveolar deadspace and intrapulmonary shunt [4][5][6]. The increase in shunt with PEEP has been noted most frequently in patients with predominantly unilateral lung disease and there is evidence that, in these circumstances, PEEP may redistribute blood flow from the well-ventilated to the diseased area of lung [7][8][9]. The application of PEEP may also decrease cardiac output and mixed venous Po 2 .…”
mentioning
confidence: 99%
“…In some patients normal values of PEEP produce little improvement in oxygenation, whilst higher values may increase alveolar deadspace and intrapulmonary shunt [4][5][6]. The increase in shunt with PEEP has been noted most frequently in patients with predominantly unilateral lung disease and there is evidence that, in these circumstances, PEEP may redistribute blood flow from the well-ventilated to the diseased area of lung [7][8][9]. The application of PEEP may also decrease cardiac output and mixed venous Po 2 .…”
mentioning
confidence: 99%
“…An alternative means of ventilating these patients is by the application of independent lung ventilation through a double‐lumen tracheal tube and the use of two separate ventilators 16 . Other studies have also found that the lateral position can improve gas exchange in animals with unilateral lung injury 17 . Hasan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Enjeti and associates [33] have shown that there is a greater reduction in regional blood flow when collapse is restricted to a segment of lung instead of a lobe in closed-chest pigs, and that the application of PEEP does not increase flow to the collapsed segment [34]. On the other hand, Hasan and colleagues [35] found that an increase in Qs/Qt in acid aspiration injury in dogs occurred at lower PEEP values when the injury was more diffuse than when it was confined to one lung.…”
Section: Discussionmentioning
confidence: 99%